The under representation of women coaches in high-performance sport - Serpell, B. G.; Harrison, D.; Dower, R.; Cook, C. J. (International Journal of Sports Science & Coaching, 2023)
High-performance sport is still not appropriately addressing issues that perpetuate women's underrepresentation in elite sport coaching and leadership. Therefore, it is also unlikely representation for other minority groups in high-performance sport will be achieved any time soon. For high-performance sport to progress, there is an opportunity to create environments that foster a variety of coaching styles with diverse racial, ethnic and gender identities. This paper points to statistics from elite football and Olympic sports to highlight the issue of the underrepresentation of women coaches in high-performance sport and draws upon a range of literature to inform an evidence-based and strategic approach to designing development in the context of increasing coach and leader gender diversity in these settings. It explores leadership in high-performance sport, learning and development, and high-performance sport environments. We argue future focused development should prepare high-performance sport leaders to intervene at an environmental level where they provide leadership, facilitate performance enablers, and engage athletes and performance staff to shape cultural change.